BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN POSYANDU LANSIA - Hamzah, Hamzah; Janah, Esti Nur; Kurniawati, Lia; Rosyidah, Alif Nurul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Based on an initial survey, Puskesmas Dolok Masihul is one of the health centers located in the Serdang Bedagai region that actively implements the Elderly Posyandu program. data through the Dolok Masihul health center profile data, the elderly age in the dolok masihul health center work area is 3,378 people. However, the number who utilize the elderly Posyandu is only 40%. The purpose of the study was to determine the factors with the utilization of the elderly posyandu. The research design used in this study was cross sectional. The research was conducted in the working area of the Dolok Masihul Health Center. The research was conducted in July 2023. The population is all elderly people aged more than 60 years who live in the Dolok Masihul Health Center working area which amounts to 300 people. The sample amounted to 73 people. The sampling technique used in this study was incidental sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed that there was a relationship between family support (p value: 0.014) and distance to health care facilities (p value: 0.000) on the utilization of elderly posyandu. It is recommended for the Puskesmas to include the role of the elderly family in supporting the utilization of the elderly posyandu. Provide an understanding to family members how important it is to assist the elderly during posyandu, and a sense of ownership to the elderly that the posyandu actually belongs to the community so that there is awareness of the elderly to utilize the posyandu.Keywords: Family Support, Elderly, Posyandu.